Pattern of lung volumes in patients with sighing breathing. - Aljadeff, G. (1993)
BACKGROUND--Sighing breathing is observed in subjects suffering from anxiety with no apparent organic disease. METHODS--Lung volumes and expiratory flow rates were measured in 12 patients with a sighing pattern of breathing and in 10 normal subjects matched for age, gender, and anthropometric data. In both groups the measurements were made by spirographic and plethysmographic techniques. In normal subjects functional residual capacity (FRC) and residual volume (RV) were measured during normal breathing and again during simulated sighing breathing to exclude technical artifacts resulting from hyperventilation during measurement by the helium closed circuit method. RESULTS--Patients with a sighing pattern of breathing had a normal total lung capacity (TLC) but significantly different partitioning of lung compartments compared with normal subjects. The vital capacity (VC) was lower when measured by both spirographic and plethysmographic methods and RV was higher. The forced expiratory volume in one second (FEV1) was also lower in patients with sighing breathing. The FEV1/VC and the maximal expiratory flow rates at 50% and at 25% of the forced vital capacity (V50 and V25) were normal and similar in both groups. In normal subjects there were no differences in RV when measured during quiet or simulated sighing breathing. CONCLUSIONS--Subjects with sighing breathing have a normal TLC with a higher RV and lower VC than normal subjects. There was no obvious physiological or anatomical explanation for this pattern.